2016
DOI: 10.1103/physrevb.93.134427
|View full text |Cite
|
Sign up to set email alerts
|

Homodyne-detected ferromagnetic resonance of in-plane magnetized nanocontacts: Composite spin-wave resonances and their excitation mechanism

Abstract: This work provides a detailed investigation of the measured in-plane field-swept homodynedetected ferromagnetic resonance (FMR) spectra of an extended Co/Cu/NiFe pseudo spin valve stack using a nanocontact (NC) geometry. The magnetodynamics are generated by a pulsemodulated microwave current and the resulting rectified dc mixing voltage, which appears across the NC at resonance, is detected using a lock-in amplifier. Most notably, we find that the measured spectra of the NiFe layer are composite in nature and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…It is worth mentioning that those were the very first simulations that stud ied ultrafast and picosecond magnetization dynamics simulta neously in largescale magnetic structures. Recently, micromagnetic modeling was also employed to reveal the origin of the asymmetric lineshape in socalled all metallic pseudo spin valves driven by RF currents injected through the nanocontact [198]. It was demonstrated that, in contrast to the direct current driven case, the microwave Oersted field generated by the nanocontact provides a broad band excitation of the propagating exchangedominated spin waves.…”
Section: Spin-waves and Magnonicsmentioning
confidence: 99%
“…It is worth mentioning that those were the very first simulations that stud ied ultrafast and picosecond magnetization dynamics simulta neously in largescale magnetic structures. Recently, micromagnetic modeling was also employed to reveal the origin of the asymmetric lineshape in socalled all metallic pseudo spin valves driven by RF currents injected through the nanocontact [198]. It was demonstrated that, in contrast to the direct current driven case, the microwave Oersted field generated by the nanocontact provides a broad band excitation of the propagating exchangedominated spin waves.…”
Section: Spin-waves and Magnonicsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] However, the dynamics of the collective coordinates also depends strongly on the spin-wave amplitude ρ. Since the spin-wave amplitude depends on the frequency of the applied excitation field [25][26][27][28] it is the spatial profile of the applied excitation field that plays the main role in determining the frequency dependence of the domain wall velocity in some of these studies.…”
Section: Equations Of Motionmentioning
confidence: 99%
“…The spatial profile of the microwave source determines how the spin-wave amplitude depends on the driving frequency. [25][26][27][28] We derive a special case of Kalinikos' general formula 25 and show that the spin-wave amplitude is proportional to the Fourier sine transform of the source profile. We then use the dependence of the spin-wave amplitude on the microwave frequency to find consistent results for how the domain wall velocity depends on the driving frequency in the numerical and analytical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…To accurately determine M eff of the [Co/Ni] free layer, spin-torque ferromagnetic resonance (ST-FMR) [36][37][38][39][40] measurements were performed on the He + -irradiated STNOs (see details in supplemental materials [41]). The fluence information and the obtained effective magnetization µ 0 M eff are presented in Table I.…”
mentioning
confidence: 99%